Disappearance of partonic collectivity in √sNN=3GeV Au+Au collisions at RHIC - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physics letters, 2022)
We report on the measurements of directed flow v1 and elliptic flow v2 for hadrons (π±, K±, KS0, p, ϕ, Λ and Ξ−) from Au+Au collisions at sNN=3GeV and v2 for (π±, K±, p and p‾) at 27 and 54.4GeV with the STAR experiment. While at the two higher energy midcentral collisions the number-of-constituent-quark (NCQ) scaling holds, at 3GeV the v2 at midrapidity is negative for all hadrons and the NCQ scaling is absent. In addition, the v1 slopes at midrapidity for almost all observed hadrons are found to be positive, implying dominant repulsive baryonic interactions. The features of negative v2 and positive v1 slope at 3GeV can be reproduced with a baryonic mean-field in transport model calculations. These results imply that the medium in such collisions is likely characterized by baryonic interactions.
Online verfügbar 3 März 2022, Artikelversion 10 März 2022
*STAR Collaboration: M.S. Abdallah, I.M. Deppner, N. Herrmann, Y. Söhngen, P. Weidenkaff [und 393 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, NN ist dabei tiefgestellt
Gesehen am 20.02.2023